Micra Leadless and Transvenous Pacemaker: A Single‐Center Comparative Study of QRS Wave Duration Resulting From Different Pacing Sites - Yichi Yu; Xiaomin Yang; Xiaoming Lian; Yan Zhao; Bo Liu; Xiangfei Feng; Qunshan Wang; Yigang Li (Annals of Noninvasive Electrocardiology)
ABSTRACT Objective To compare the paced QRS duration on different sites in age‐, gender‐, and indication‐matched patients implanted with Micra leadless pacemakers and conventional transvenous pacemakers (TV‐PM). Method A total of 82 patients from Xinhua Hospital, Shanghai Jiaotong University, were enrolled, including two groups of 41 patients matched according to gender, age, and pacemaker indications, who underwent Micra and TV‐PM implantations, respectively. The baseline data of the patients, the pacing site described using three‐ and nine‐partition methods, and the paced QRS duration on 12‐lead electrocardiogram were then analyzed. Results Overall, patients in our population were on average 79.2 years of age and mostly male (75.6%). Atrioventricular node dysfunction was the most common indication (56.1%) for pacemaker therapy. Mid‐septum, especially Site 5, is the implantation site for most patients in both groups. Micra (145 ms) and TV‐PM (133 ms) both had the narrowest‐paced QRS at high septum, but Micra may exhibit significantly more reduced QRS duration than TV‐PM at low septum (Micra vs. TV‐PM: 143.0 [142.8–156.5] ms vs. 163.5 ± 17.5 ms, p = 0.044). Conclusion The narrowest‐paced QRS complex for Micra leadless pacemakers is achieved at high septum, and pacing at low septum by Micra may acquire shorter QRS duration than conventional TV‐PM.